Impact du changement climatique sur les risques littoraux en NPDC - Julien Hénique (VertigO)
Nowadays, the services of the State in Nord-Pas-de-Calais region carry an ambitious program of studies aiming at appreciating the effects of climate change on the coastal region. This program is issued from a report delivered in September, 2005 to the Prefect of region, report which recommended to monitor the effects of climate change on this risk, in spite of immediate moderate risks of submersion.A working program was therefore proposed by the regional direction of environment, spatial planning and housing (DREAL) to the Prefect in April, 2006, calling upon all the services of the State in region. A piloting committee which at first only included the services of the State was constituted, then this committee was enlarged to some representatives of local authorities.This piloting committee is a guarantee of a good appropriation of the program between all regional stakeholders. An information meeting for all the elected representatives of the coastal region is also programmed yearly, out of concern of transparency and sensitisation about these phenomena toward all local stakeholders. Finally, regular contacts with foreign colleagues strengthen the coherence of this local program with other European initiatives and develop the sharing of experiments on these topics.